Vloga regij v vedenju potrošnikov na velikem trgu - Ding, Zhonghui (Annales. Series historia et sociologia, 2025)
This paper investigates the influence of regional diversity on consumer characteristics in large markets, using China as a case study. The study aims to explore how regional cultural values and consumer traits vary across different regions and proposes a regionally tailored approach to marketing strategy formulation. Data were col-lected from three socio-economically diverse regions in China, with three tiered cities surveyed in each region to account for intraregional variations in population size, socio-economic development, and administrative hierarchy. The total sample included 1,062 respondents. Methodologically, the study adapted established and validated scales to measure four dimensions of personal cultural values, consumer ethnocentrism, and consumer innovativeness, enabling an empirical examination of regional differences. The findings reveal significant inter--regional variations in intolerance of ambiguity, tradition, and consumer innovativeness. For instance, consumers in the Northern region exhibited lower levels of intolerance of ambiguity and innovativeness compared to other regions, while consumers in the Eastern region placed the least emphasis on tradition. These results underscore the importance of recognizing and addressing regional differences in consumer behaviour. The study concludes that international marketers should move away from a one-size-fits-all approach and instead adopt regionally segmented strategies that account for the unique cultural and economic characteristics of each region. By doing so, marketers can better target and tailor their offerings to local consumer needs, thereby enhancing the effectiveness of their strategies in large and diverse markets like China
Keywords: China; consumer behaviour; Kitajska; marketing; trženje; vedenje potrošnikov